Metais pesados em solos sob aplicação de dejetos líquidos de suínos em duas microbacias hidrográficas de Santa Catarina - Mattias, Jorge Luis (2006)
The application of pig slurry in agricultural soils can be an efficient form of nutrients cilcle and one of the best alternative for discard and minimizing his pollutant potential. However, the differences between his composition and the needs of the plants, especially of trace elements, it hinders her more rational use. The composition of the pig slurry is reflex of the feeding type offered to the animals, which usually contains larger amounts of nutrients than the required for the animals. That fact, associate to systematic applications of pig slurry in the soils can cart in accumulations, becoming pollution source not punctual in the environment. The present work was elaborated with the objective in identifying the possible sources of contamination of the soils with trace elements, to esteem the capacity of the soils in receiving successive applications of metals and also verify if the soils that receive systematic applications of pig slurry with high tenors of metals can in a small space of time resent problems of environmental contamination. Three studies were conduced in the watersheed Rio Coruja/Bonito and Lajeado Fragosos in Santa Catarina state. In the study 1 it was looked for to evaluate the sources of entrance of trace elements in the environment. In the study 2 it was looked for to evaluate the current state of trace elements in the soils under application and the main attributes of the soils that influence in her retention. In the study 3 it was looked for to evaluate the maximum capacities of retention of trace elements of the soils and the interaction degree with the soils. In the first samples of feeds and pig slurry were collected in 12 properties of each one of the watersheeds and the total amounts of the elements of the feeds were analyzed. In the second study collections of soils were accomplished in the 12 properties, representative of the three main classes of soils of watersheeds, the total and available amounts of trace elements were analyzed in the soils, the mineralogy and the organic matter of the soils. And in the third study they were applied doses of trace elements to the soils to esteem the retention capacity for the elements considered pollutants, it was also esteemed the capacity of liberation of the elements retained starting from a disturbance. The obtained results show that it is made a super-dosage of trace elements to the swine in the feeds and these are transferred to the pig slurry, that, allied the great applied amounts elevate the levels in soils. The attributes of the soils responsible for the retention of the trace elements are not capable to the systematic reception of the pig slurry, and, the annually applied amounts don't reflect the amounts found on the soils. The soils of watersheeds didn't reach his maximum capacity of retention for the elements of larger addition to the soils, even if being these lowers. Therefore, practice that propitiate to the soils improvement of the attributes responsible for the retention of the trace elements are pressing to reduce the probability of environmental contaminations.